An Experiment of Introducing ePortfolio to Evaluate Students in the Tunisian Context - Mhiri Sellami, Hedia (International Journal of Emerging Technologies in Learning (iJET), 2012)
We present an experiment of ePortfolio use as a tool to assess students in a module taught in a master degree class. Each student is required to deposit an abstract for each chapter in his own ePortfolio. A mark is given to each assignment and then the average of all these marks is considered for the success criteria. At the end of the semester, students are submitted a questionnaire in order to evaluate their appreciation of the ePortfolio use. The formal analysis of the questionnaire confirms our overall idea that most students appreciate the ePortfolio use. They also express their wishes to extend the ePortfolio to the other modules. The teacher's perspective for this experiment is also presented.